X-Ray Analysis on Ceramic Materials Deposited by Sputtering and Reactive Sputtering for Sensing Applications - Gazia, Rossana; Chiodoni, Angelica; Celasco, Edvige; Bianco, Stefano; Mandracci, Pietro (IntechOpen, 2012)
None